Bridging in AFP-manufactured sandwich structures: investigation of the influence of material tackiness, process parameters and path planning - Nils Siemen; Klaus Heller; Marc van Bussel; Eduardo Segarra; Leo Körber; Klaus Drechsler (Advanced Manufacturing: Polymer & Composites Science, 2025)
Several studies have shown that using Automated Fiber Placement (AFP) technology can improve productivity and resource efficiency in manufacturing sandwich structures. In this process the bridging effect occurs, which negatively impacts the processability and component quality. The aim of our work is to investigate the reduction of the bridging effect by analyzing the influence of prepreg and adhesive film tackiness, path planning parameters, and AFP process parameters on the bridging effect. To achieve this, the tackiness was first characterized in the probe tack test and then AFP lay-up tests were carried out. Suitable tack levels were identified to reduce the bridging effect. The results indicate that the unbonded area can be reduced by a factor of up to 6.9 by adjusting path planning parameters and process parameters statistically significantly influence the bridging effect. In conclusion, guidelines were deduced for sandwich structure's productive, sustainable, and high-quality AFP manufacturing.